Clinical Efficacy of Solifenacin in the Management of Diabetes Mellitus-Associated Versus Idiopathic Overactive Bladder Symptoms: A Multicenter Prospective Study - Choi, Hoon (Int Neurourol J, 2018)
PURPOSE: To compare the clinical efficacy of anticholinergics for managing diabetes mellitus-associated overactive bladder (DM OAB) versus idiopathic overactive bladder (OAB) in Korean women. METHODS: We conducted a multicenter, prospective, parallel-group, open-label, 12-week study. Women (20–65 years old) with OAB symptoms for over 3 months were assigned to the DM OAB and idiopathic OAB groups. Changes in the Overactive Bladder Symptom Score (OABSS), urgency, urinary urgency incontinence, nocturia, daytime frequency according to a voiding diary, uroflowmetry, and postvoid residual urine volume (PVR) at the first visit (V1), week 4 (V2), and week 12 (V3) were compared. RESULTS: No significant difference was found between the baseline patient characteristics of the DM OAB and idiopathic OAB groups. Treatment with solifenacin was associated with improvements in urgency, urinary urgency incontinence, nocturia, frequency according to a voiding diary, and the total OABSS between V1 and V2 and between V1 and V3. Moreover, a significant improvement in urgency and urge incontinence was found between V2 and V3 in the DM OAB group. However, no significant changes were found in any other parameters. There were no significant differences between the DM OAB group and the idiopathic OAB group except for urgency and urge incontinence at V2 (3.71 vs. 2.28 and 0.47 vs. 0.32, respectively). CONCLUSIONS: The patients who received solifenacin demonstrated improved urgency, urinary urgency incontinence, nocturia, frequency according to a voiding diary, and total OABSS. Management with solifenacin was equally effective for both DM-related OAB and idiopathic OAB.